2018
DOI: 10.3889/oamjms.2018.023
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Complex Treatment in Mixed Leg Ulcers – A Case Report of Vascular, Surgical and Physical Therapy

Abstract: BACKGROUND:Leg ulcers are a burden to patients, their families and society. The second most common cause of chronic leg ulcers is the mixed arterio-venous type. An 80-year-old female patient presented to our department due to painful enlarging chronic leg ulcer of mixed arteriovenous origin on her left lower leg. She suffered from peripheral arterial occlusive disease stage I and chronic venous insufficiency Widmer grade IIIa, and a number of comorbidities.AIM:The aim of our ulcer treatment was a complete and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…[15][16][17][18][19] To our knowledge, one randomized control trial and one observational trial have been conducted investigating the effect of CO 2 -enriched water on chronic wound treatment in humans, one observational study using transcutaneous application of CO 2 in acute and chronic wounds, and one randomized controlled study using subcutaneous CO 2 injections in chronic wound treatment. 13,14,20 All mentioned studies confirmed a positive influence on the healing of chronic wounds. In our opinion, transcutaneous application of gaseous CO 2 has some advantages compared with the other two application methods: it is not invasive like subcutaneous injections of CO 2 and it does not moisturize the wound area like CO 2 -enriched water.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…[15][16][17][18][19] To our knowledge, one randomized control trial and one observational trial have been conducted investigating the effect of CO 2 -enriched water on chronic wound treatment in humans, one observational study using transcutaneous application of CO 2 in acute and chronic wounds, and one randomized controlled study using subcutaneous CO 2 injections in chronic wound treatment. 13,14,20 All mentioned studies confirmed a positive influence on the healing of chronic wounds. In our opinion, transcutaneous application of gaseous CO 2 has some advantages compared with the other two application methods: it is not invasive like subcutaneous injections of CO 2 and it does not moisturize the wound area like CO 2 -enriched water.…”
Section: Introductionmentioning
confidence: 77%
“…As noted by many authors, CO 2 therapy has a vasodilatory effect probably influenced by a NO-dependent pathway. 13,14,17,[23][24][25][26] Savin as well as Sato confirmed vasodilatation and increased blood flow after a single exposure to CO 2 therapy compared with a placebo in humans. 17,26 Minamiyama and Yamamoto used intravital microscopy to confirm subcutaneous vasodilatation after CO 2 therapy in rats.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Лечение хронических ран остается одной из нерешенных проблем, которой занимаются специалисты в области пластической хирургии и хирургической инфекции во всем мире [1][2][3][4]. Мировая статистика свидетельствует о том, что частота встречаемости этого заболевания за последние годы не имеет тенденции к уменьшению [5,6,7].…”
Section: Introductionunclassified